Facile Synthesis of Large and Thin TiS2 Sheets via a Gas/Molten Salt Interface Reaction. Issue 5 (16th February 2015) - Tan, Mingsheng; Wang, Zhiyong; Peng, Junjun; Jin, Xianbo
Abstract : Highly crystalline hexagonal titanium disulfide (TiS2 ) sheets were synthesized at the gas/liquid interface between TiCl4 vapor and the dissolved Na2 S in equimolar NaCl–KCl melts at temperatures between 700°C and 850°C. TiS2 sheets with sizes of about 10–20 μm and thicknesses of about 50–200 nm have been collected at 700°C–750°C, and much bigger (50–100 μm in sizes) and thicker (1–5 μm in thickness) TiS2 sheets were obtained at 850°C. The mass transfer preferential growth of an interphase layer and the thermodynamically preferential enlargement of the (001) plane of the hexagonal TiS2 crystal were thought to have led the formation of large and thin TiS2 sheets in this proposed gas/liquid interface process. Due to the density difference, the ripe TiS2 sheets sank into the melt allowing the continuing preparation of TiS2 sheets. These TiS2 sheets could spontaneously assemble to TiS2 membranes or be ultrasonically exfoliated to few‐layer TiS2 sheets with thicknesses less than 5 nm. The presented approach should be potentially extendable to the synthesis of large and thin sheets of other layered metal dichalcogenides in large scale.